Data intermediary - Heleen Janssen; Jatinder Singh (Internet Policy Review, 2022)
Data intermediaries serve as a mediator between those who wish to make their data available, and those who seek to leverage that data. The intermediary works to govern the data in specific ways, and provides some degree of confidence regarding how the data will be used.
Keywords: 300; Data intermediaries; Data protection; Data governance; Accountability; Trust; Data commons